RSSI-based localisation algorithms using spatial diversity in wireless sensor networks. (2015) - Hamdoun, Safa; Rachedi, Abderrezak; Benslimane, Abderrahim
Many localisation algorithms in wireless sensor networks (WSNs) are based on received signal strength indication (RSSI). Although these methods present some advantages in terms of complexity and energy consumption, RSSI values especially in indoor environments, are very unstable due to fading. In this paper, we propose a comparative study of RSSI-based localisation algorithms using spatial diversity in WSNs. We consider different kinds of single/multiple antenna systems: single input single output (SISO) system, single input multiple output (SIMO) system, multiple input single output (MISO) system and multiple input multiple output (MIMO) system. We focus on the well known trilateration and multilateration localisation algorithms. Three diversity combining techniques at the receiver are used: maximal ratio combining (MRC), equal gain combining (EGC) and selection combining (SC). The obtained results show that using multiple antennas at both the transmitter and receiver sides present better performance than using multiple antennas at only one side. We also conclude that MRC diversity combining technique outperforms EGC that as well outperforms SC.